Spatial-temporal soil-water content dynamics in toposequences with different plant cover in a tropical semi-arid region - Makeison Moreira de Sousa, Marcos (Revista Ciência Agronômica, 2021)
Anthropogenic effects on the natural environment and on soil moisture in the tropical semi-arid region have not yet been determined. As such, the temporal variability of soil moisture was investigated in two toposquences under different types of plant cover: i) Caatinga under regeneration since 1978 (CReg); ii) Caatinga thinned by 40% (CThn). The research was carried out in two catchment located in the northeast of Brazil, with an area of 2.06 and 1.15 ha for CReg and CThn respectively. Soil moisture was determined using the gravimetric method. Three random soil samples were collected daily from the upper, middle and lower section of each catchment, giving a total of nine daily collections and 1620 collection in the period. CThn displayed higher values and a longer period for soil moisture. The lower section of the catchment showed values for soil moisture that were higher and statistically different (p < 0.05) from the other sections. The increasing value for the correlation between moisture and the seven days of antecedent rainfall indicates a low rate of decrease for soil moisture.